2016
DOI: 10.1016/j.foodchem.2016.02.080
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of ω-3 fatty acids in nanoemulsion-based delivery systems fabricated from natural emulsifiers: Sunflower phospholipids

Abstract: Nanoemulsions have considerable potential for encapsulating and delivering ω-3 fatty acids, but they are typically fabricated from synthetic surfactants. This study shows that fish oil-in-water nanoemulsions can be formed from sunflower phospholipids, which have advantages for food applications because they have low allergenicity and do not come from genetically modified organisms. Nanoemulsions containing small droplets (d<150 nm) could be produced using microfluidization, by optimizing phospholipid type and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(49 citation statements)
references
References 39 publications
3
32
2
2
Order By: Relevance
“…The solutes addition on the aqueous phase as osmotic agents helps to balance the capillary pressure and coalescence . The encapsulation of active compounds can provide protection against degradation during the manufacturing and shelf life, preventing loss of nutritional value …”
Section: Introductionmentioning
confidence: 99%
“…The solutes addition on the aqueous phase as osmotic agents helps to balance the capillary pressure and coalescence . The encapsulation of active compounds can provide protection against degradation during the manufacturing and shelf life, preventing loss of nutritional value …”
Section: Introductionmentioning
confidence: 99%
“…The free fatty acids released from lipid digestion contributed to formation of anionic species that further increased the negative charge (Salvia‐Trujillo, Qian, Martin‐Belloso, & McClements, 2013a). However, the fish oil emulsion showed a relatively lower zeta potential after digestion, which was possibly because that the free fatty acids were not fully released as a result of its low degree of lipolysis under intestinal conditions (Komaiko, Sastrosubroto, & McClements, 2016; Walker, Decker, & McClements, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, LCT forms mixed micelles with relatively large hydrophobic domains suitable to deliver beta‐carotene (Zhang et al., 2016). However, the bioaccessibility of fish oil carried beta‐carotene was significantly lower than corn oil or palm oil, which was probably because of its special lipid composition (Komaiko et al., 2016; Ulven et al., 2011; Walker et al., 2015). Qian et al., (2012b) applied orange oil abundant of short‐length carbon chain to form beta‐carotene nanoemulsion, in which the bioaccessibility of beta‐carotene was close to zero.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of water binding agents on the rate of lipid oxidation depends on the water activity but in the presence of glycerol, the prooxidant effect of water was found to predominate at all water activities (Heidelbaugh and Karel ). The presence of electrolytes increases the interfacial tension due to salting out of the emulsifiers leading to decreased emulsion stability (Komaiko and others ).…”
Section: The Participation Of Different Molecular Species In the Oxidmentioning
confidence: 99%
“…Different emulsifiers are expected to have different effects on these opposing factors in microemulsions enriched in n‐3 fatty acids. Other factors can affect the performance of emulsifiers as, for example, it was found that the effects of sunflower phospholipids is markedly affected by pH and ionic strength (Komaiko and others ).…”
Section: Process and Engineering Possibilitiesmentioning
confidence: 99%